Isolation and genetic characterization of canine parvovirus CPV in a Malayan tiger - Nur Farahiya, Ahmad Nadzri; Kumar, Kiven; Yasmin, Abd Rahaman; Omar, Abdul Rahman; Camalxaman, Siti Nazrina (MDPI, 2021)
Naïve Felidae in the wild may harbor infectious viruses of importance due to cross-species transmission between the domesticated animals or human–wildlife contact. However, limited information is available on virus shedding or viremia in the captive wild felids, especially in Malaysia. Four infectious viruses of cat, feline herpesvirus (FHV), feline calicivirus (FCV), canine distemper virus (CDV), and canine parvovirus (CPV), were screened in leopards, feral cats, and tigers in Malaysia based on virus isolation in Crandell-Rees feline kidney (CRFK) cells, PCR/RT-PCR, and whole-genome sequencing analysis of the positive isolate. From a total of 36 sera collected, 11 samples showed three consecutive cytopathic effects in the cell culture and were subjected to PCR using specific primers for FHV, FCV, CDV, and CPV. Only one sample from a Malayan tiger was detected positive for CPV. The entire viral genome of CPV (UPM-CPV15/P. tigris jacksoni; GenBank Accession number MW380384) was amplified using the Sanger sequencing approach. Genome sequencing of the isolate revealed 99.13, 98.65, and 98.40% close similarity to CPV-31, CPV-d Cornell #320, and CPV-15 strains, respectively, and classified as CPV-2a. Time-scaled Bayesian Maximum Clade Credibility tree for the non-structural (NS) genes of CPV showed a close relationship to the isolates CPV-CN SD6_2014 and KSU7-SD_2004 from China and USA, respectively, while the capsid gene showed the same ancestor as the FPV-BJ04 strain from China. The higher evolution rate of the capsid protein (CP) (VP 1 and VP2) [1.649 × 10−5 (95% HPD: 7.626 × 10−3 to 7.440 × 10−3)] as compared to the NS gene [1.203 × 10−4 (95% HPD: 6.663 × 10−3 to 6.593 × 10−3)] was observed in the CPV from this study, and fairly higher than other parvovirus species from the Protoparvovirus genus. Genome sequencing of the isolated CPV from a Malayan tiger in the present study provides valuable information about the genomic characteristics of captive wild felids, which may add information on the presence of CPV in species other than dogs.